2016
DOI: 10.1016/j.nec.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Surgical Intervention in Traumatic Brain Injury

Abstract: The general consensus to optimize the care for severe TBI patients is management at specialized neurotrauma centers with neurosurgical and neurocritical care support and the use of guidelines-based standardized protocols. Over the last decade, significant efforts have been made to define neurotrauma treatment guidelines. However, it is important to recognize the heterogeneity of TBI and that the "one-size-fits-all approach" may not always be appropriate for these patients. Knowledge synthesis activities in neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 105 publications
(129 reference statements)
0
13
0
Order By: Relevance
“…Therefore, we recommend the use of a less strict definition of the indications for surgery in order to improve the treatment success rate in patients with BFCs. Traditional guidelines suggest that surgical treatment should be performed immediately if the following signs are present in patients with traumatic brain injuries: contused volume of the frontal, temporal, or parietal lobes > 20 mL and a midline shift > 5 mm with basal cistern compression [ 7 ]. We suggested that surgical treatment is indicated if (1) conscious patients experience mild disturbances of consciousness and restlessness, miosis, slow pupillary light reflex, increased blood pressure, faster pulse and respiration, and increased muscle tone; (2) dynamic CT monitoring shows a trend toward increased primary and scattered contusion spots or significantly expanded edema and compression of the frontal horn of the lateral ventricle; and (3) significant enlargement of unilateral contusions, or intracerebral hematoma and a > 5 mm shift of the anterior midline to the contralateral side, which could be accompanied by decreased consciousness.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we recommend the use of a less strict definition of the indications for surgery in order to improve the treatment success rate in patients with BFCs. Traditional guidelines suggest that surgical treatment should be performed immediately if the following signs are present in patients with traumatic brain injuries: contused volume of the frontal, temporal, or parietal lobes > 20 mL and a midline shift > 5 mm with basal cistern compression [ 7 ]. We suggested that surgical treatment is indicated if (1) conscious patients experience mild disturbances of consciousness and restlessness, miosis, slow pupillary light reflex, increased blood pressure, faster pulse and respiration, and increased muscle tone; (2) dynamic CT monitoring shows a trend toward increased primary and scattered contusion spots or significantly expanded edema and compression of the frontal horn of the lateral ventricle; and (3) significant enlargement of unilateral contusions, or intracerebral hematoma and a > 5 mm shift of the anterior midline to the contralateral side, which could be accompanied by decreased consciousness.…”
Section: Discussionmentioning
confidence: 99%
“…EDH requires urgent neurosurgical evacuation. With prompt intervention, prior to herniation or local compression, the outcome from an EDH may be good, as there is often little underlying neuronal damage compared to subdural hematomas (SDHs), which often have associated direct parenchymal injury and edema …”
Section: Mechanisms and Complications Of Injurymentioning
confidence: 99%
“…[ 1 ] Surgical decompressive craniectomy (DC) is recommended in such cases, intervention being aimed at lowering ICP to minimize secondary brain damage. [ 2 3 ]…”
Section: Introductionmentioning
confidence: 99%